High-precision neural stimulation by a highly efficient candle soot fiber optoacoustic emitter - Chen, Guo; Shi, Linli; Lan, Lu; Wang, Runyu; Li, Yueming; Du, Zhiyi; Hyman, Mackenzie; Cheng, Ji-Xin; Yang, Chen (Frontiers in Neuroscience, 2022)
Highly precise neuromodulation with a high efficacy poses great importance in neuroscience. Here we developed a candle soot fiber optoacoustic emitter (CSFOE), capable of generating a high pressure of over 10 MPa with a central frequency of 12.8 MHz, enabling highly efficient neuromodulation in vitro. The design of the fiber optoacoustic emitter, including the choice of the material and the thickness of the layered structure, was optimized in both simulations and experiments. The optoacoustic conversion efficiency of the optimized CSFOE was found to be ten times higher than the other carbon-based fiber optoacoustic emitters. Driven by a single laser, the CSFOE can perform dual-site optoacoustic activation of neurons, confirmed by calcium (Ca2+) imaging. Our work opens potential avenues for more complex and programmed control in neural circuits using a simple design for multisite neuromodulation in vivo.